Life skills and teaching skills: A correlational study of prospective teacher - Linda Tri Antika; Moch. Haikal; Agus Budiyono (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2022)
Prospective teachers of 21st century need to prepare themselves in carrying out their profession as professional teacher candidates, namely by having good teaching skills. In addition, skills that support teaching skills also need to be possessed by prospective teacher students, such as life skills. The purpose of this research was to explain the relationship of life skills and teaching skills of prospective teacher students. The subjects in this study were fourth semester students of Biology Education Department, Faculty of Teacher Training and Education (FKIP), Universitas Islam Madura. This research was a quantitative study using a correlational research design to explain the relationship between predictors (life skills) and criteria (teaching skills). Life skills data were obtained from life skills assessment sheet score. Life skills assessment sheet consist of four skills, namely: interpersonal skill, shared goal setting and accomplishment, responsibility, and managing. The four skills have their indicators and score levels. Teaching skills data were obtained from teaching skills assessment sheet score which had four aspects of assessment, namely: opening learning, main activities, closing learning, and supporting factors. The result showed statistically significant correlation between life skills and teaching skills of prospective teachers.